2014
DOI: 10.1177/1541931214581139
|View full text |Cite
|
Sign up to set email alerts
|

Postural stress experienced by vaginal surgeons

Abstract: Increasing attention has been drawn to the prevalence of work-related musculoskeletal disorders (MSDs) among surgeons in various medical specialties; however, the risk of work-related MSDs among gynecologic surgeons has not received much attention. This study aimed to investigate the postural load among gynecologic surgeons for various surgical tasks during vaginal surgery. The frequency and percentage of duration of awkward upper body postures experienced by vaginal surgeons during eleven different vaginal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, impact of these novel techniques on the Generally, workload has been considered as "costs incurred by a human operator to achieve a particular level of performance" and evolves from interactions between task demands, circumstances and personal skills, behavior, and perceptions (Noyes and Bruneau, 2007). For physical workload, there are observational methods to analyze body posture (Zhu et al, 2014(Zhu et al, , 2017 and more recently more objective measures such as Inertial Movement Units (IMUs) (Morrow et al, 2016). Workload can also be measured objectively with EMG, heart rate or using subjective measures, such as the body part discomfort (Kuorinka et al, 1987), NASA-TLX (Hart and Staveland, 1988), and SURG-TLX (Wilson et al, 2011).…”
Section: Workload In Rasmentioning
confidence: 99%
“…However, impact of these novel techniques on the Generally, workload has been considered as "costs incurred by a human operator to achieve a particular level of performance" and evolves from interactions between task demands, circumstances and personal skills, behavior, and perceptions (Noyes and Bruneau, 2007). For physical workload, there are observational methods to analyze body posture (Zhu et al, 2014(Zhu et al, , 2017 and more recently more objective measures such as Inertial Movement Units (IMUs) (Morrow et al, 2016). Workload can also be measured objectively with EMG, heart rate or using subjective measures, such as the body part discomfort (Kuorinka et al, 1987), NASA-TLX (Hart and Staveland, 1988), and SURG-TLX (Wilson et al, 2011).…”
Section: Workload In Rasmentioning
confidence: 99%
“…7,11,14,15 The postural risk categories, calculated with the modified rapid upper limb assessment, stayed in moderate or severe risk (category 3 or 4) for the upper body Comparison of the percentage of time during the vaginal procedure spent in risk category 3 ajog.org for a majority of time, which is a matter of concern. Zhu et al 10 assessed and quantified the postural load during vaginal procedures and all the surgeons stood during the entire procedure. Similar to our findings, the authors noted that the neck was most affected during vaginal surgery.…”
Section: Commentmentioning
confidence: 99%
“…6 The literature of evaluated ergonomic issues in obstetrics and gynecology is further limited. 7,[10][11][12][13][14][15][16] In gynecological surgery, the vaginal route is a traditional approach and involves working in a constrained space and in unfavorable postures for long durations. A survey of gynecological surgeons showed that 86.7% of surgeons performing vaginal surgery experienced work-related musculoskeletal discomfort.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This framework was selected because it is upper body focused and has been shown to be most effective in medium-risk conditions [35]. An emphasis was placed on the use of a framework suited to medium-risk circumstances because LS has been shown to induce prolonged low-risk non-neutral postures as well as episodic high-risk postures [10,36,37], therefore a medium risk classification seemed to be the optimal choice given these postural habits.…”
Section: Postural Assessmentmentioning
confidence: 99%